Climate dynamics of the Beloe Sea catchment area (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The climate of the Beloe Sea  catchment area (total size 717.7 km2, 714 of which belongs to Russia) is described. The territory is characterized by several geographic zones, thus substantial diversity of climatic conditions is observed. Climate variability in the region was studied using data from the longest available instrumental observations at weather stations (WS) and gauge sites of the Russian Federal Hydrometeorology and Environmental Monitoring Agency located in the study area, covering the period from the beginning of observations at the stations until 2012-2013. The data obtained were statistically processed with due regard to the research tasks. Modern observational data are analyzed to distinguish the changes in the climatic regime of the main parameters, i.e. air temperature, precipitation, sunshine length, etc. Since 1989, the stable increase of mean annual air temperature (1-2оC) over a climatic norm is observed. The most intensive warming is typical for the winter months. The analysis of changes in precipitation over the study area demonstrates the stable increase of annual sums, deviation of which from the climatic norm in the first decade of XXI century is about 50-100 mm